Considerações sobre a Formação de Preços na Pecuária de Corte - Arruda, Alessandro Gustavo Souza; Lanari, Cláudio Santoro; de Souza, Antônio Artur (Contabilidade Vista & Revista, 2009)
O artigo não possui resumo.